CD71+ Erythroid Cell Expansion in Adult Sepsis: Potential Causes and Role in Prognosis and Nosocomial Infection Prediction - Zhao, Guang-ju; Jiang, Dan-wei; Cai, Wen-chao; Chen, Xiao-Yan; Dong, Wei; Chen, Long-wang; Hong, Guang-liang; Wu, Bin; Yao, Yong-ming; Lu, Zhong-qiu (Frontiers in Immunology, 2022)
Background: Immune suppression contributes to nosocomial infections (NI) and poor prognosis in sepsis. Recent studies revealed CD71+ erythroid cells had unappreciated immunosuppressive functions. This study aimed to investigate the values of CD71+ erythroid cells (CECs) in predicting NIs and prognosis among adult septic patients. The potential factors associated with the expansion of CECs were also explored. Methods: In total, 112 septic patients and 32 critically ill controls were enrolled. The frequencies of CD71+cells, CD71+CD235a+ cells and CD45+ CECs were measured by flow cytometry. The associations between CECs and NIs and 30-day mortality were assessed by ROC curve analysis, Cox and competing-risk regression model. Factors associated with the frequency of CECs were identified by linear regression analysis. Results: The percentage of CD71+cells, CECs, CD45+CECs were higher in septic patients than critically ill controls. In septic patients, the percentage of CD71+cells, CECs and CD45+CECs were associated with NI development, while CD71+cells and CECs were independently associated with 30-day mortality. Linear regression analysis showed that the levels of interleukin (IL)-6 and interferon (IFN)-γwere positively associated with the frequencies of CD71+cells, CECs and CD45+CECs, while IL-10 was negatively associated with them. Additionally, the levels of red blood cells (RBCs) were negatively associated with the percentage of CD45+ CECs. Conclusions: CECs were expanded in sepsis and can serve as independent predictors of the development of NI and 30-day mortality. Low levels of RBCs and high levels of IL-6 and IFN-γmay contribute to the expansion of CECs in sepsis. Trial registration: ChiCTR, ChiCTR1900024887. Registered 2 Augest 2019, http://www.chictr.org.cn/showproj.aspx?proj=38645